The Impact of Teacher Competencies, Academic Supervision, and Principal Leadership on Teacher Performance in the Gambia's Government High Schools - Kebba Saine; Suryo Budi Santoso (UM Purwokerto Press, 2024)
The purpose of this study is to determine the impact of teacher competencies, academic supervisors, and principal leadership on teacher performance. A quantitative method was used in this study. A questionnaire utilizing a Likert-type of 5 rating scales was used to collect information using the survey method. The study included 125 respondents who were chosen at random from the senior high schools in Regional Education Directorate I&II. Multiple linear regression and the coefficient of determination test (R2) were used to analyze the data. According to the findings, teacher competencies, academic supervision, and principal leadership all have a positive and significant impact on teachers' performance. Leadership is necessary to guide, oversee, and regulate people, property, and challenges affecting the school, as well as to identify appropriate solutions to problems that may appear in order to achieve the desired objectives. The efforts of the vice principals and other senior teachers as supervisors can supplement the endeavors of the principal to ensure the correct execution of plans and accomplish their objectives. Academic supervision assists teachers in identifying and strengthening their weak areas in order to deliver appropriately, as well as improving their skills and performance. Activities like these could add to good working conditions, ethics, and a welcoming environment for teachers and students, as well as increasing teachers' competencies by providing them with thorough knowledge and mastery of their subject area and job in order boost their performance. This study will give insights into the factors that have a significant impact on teachers' performance.